1988
DOI: 10.1523/jneurosci.08-03-00733.1988
|View full text |Cite
|
Sign up to set email alerts
|

Development and survival of neurons in dissociated fetal mesencephalic serum-free cell cultures: I. Effects of cell density and of an adult mammalian striatal-derived neuronotrophic factor (SDNF)

Abstract: The use of CNS cultures for detection and quantification of neuronotrophic activity in the CNS has been analyzed. In particular the development, i.e., neurotransmitter uptake characteristics, and survival of dopaminergic and GABAergic neurons in fetal mouse (E13)- dissociated mesencephalic cells cultured in serum-free, hormone- supplemented medium have been assessed as a function of culture time and cell density. At all times, more than 98% of the cells were classified as neurons on the basis of immunocytochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
39
1

Year Published

1988
1988
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(49 citation statements)
references
References 65 publications
9
39
1
Order By: Relevance
“…Briefly, rostra1 mesencephalic tegmentum and corpus striatum from brains of 13-and 15-d-old mouse embryos, respectively, were dissected under the microscope in sterile conditions and dissociated mechanically. The cells were centrifuged at 45 x g for 4 min and resuspended in a serum-free medium consisting of equal volumes of Eagle's basal medium and Ham's F12, supplemented with components as reported in the preceding paper by Dal Toso et al (1988). Two milliliters of cell suspension containing the desired amounts of cells were added to collagen-coated 35-mm-diameter tissue culture dishes (Falcon).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, rostra1 mesencephalic tegmentum and corpus striatum from brains of 13-and 15-d-old mouse embryos, respectively, were dissected under the microscope in sterile conditions and dissociated mechanically. The cells were centrifuged at 45 x g for 4 min and resuspended in a serum-free medium consisting of equal volumes of Eagle's basal medium and Ham's F12, supplemented with components as reported in the preceding paper by Dal Toso et al (1988). Two milliliters of cell suspension containing the desired amounts of cells were added to collagen-coated 35-mm-diameter tissue culture dishes (Falcon).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to uptake studies, culture medium was removed, cells washed extensively with PBS containing glucose (6 gm/liter), Ca*+ (1 mM), and Mgz+ (1 mM). Assay of)H-dopamine (DA) uptake was conducted as previously described (Prochiantz et al, 198 1;Dal Toso et al, 1988). With the exception of kinetic studies, 5 x lo-* M 3H-DA was routinely employed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…media die rapidly. Several laboratories (21)(22)(23)(24)(25)(26), including ours The plates were air dried, dehydrated, and then scored for the (16,17,19,20,(27)(28)(29)(30)(31), have demonstrated that the addition of number of NSE neurons by a n observer blinded to treatment striatal extracts containing trophic activity directed at mesencehistory. Using a phase-contrast, inverted microscope Fluovert phalic neurons reduces this ncuronal death rate and stimulates (Leitz, Leipsig, Germany) the center strip of each well was the growth of DA neurons.…”
Section: Da Dopac Str Cbmentioning
confidence: 99%